2020
DOI: 10.29342/cnj.v3i1.101
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Antara Lokasi Stroke Dengan Gangguan Kognitif Pada Penderita Stroke Di Rsup Sanglah Denpasar

Abstract: Latar Belakang Kasus stroke mengalami kecenderungan peningkatan baik dalam kematian maupun kecacatan. Morbiditas paska stroke dapat berupa masalah fisik, psikis dan kognitif. Risiko gangguan fungsi kognitif meningkat sebesar tiga kali lipat setelah suatu awitan stroke dan 25-50% diantaranya akan berkembang menjadi demensia paska stroke. Penilaian gangguan fungsi kognitif pada penderita paska stroke sangat penting oleh karena gangguan fungsi kognitif berhubungan dengan luaran fungsional yang buruk, tingka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…The results of this study are in accordance with the previous studies conducted on 100-night shift nurses, found 69% of subjects with low MoCA-INA values and cognitive impairment [10]. Other previous studies were in line with the results of this current study, conducted research at Sanglah Hospital Denpasar with the results of a decrease in cognitive function scores on nurses with a shift work system [5], [8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are in accordance with the previous studies conducted on 100-night shift nurses, found 69% of subjects with low MoCA-INA values and cognitive impairment [10]. Other previous studies were in line with the results of this current study, conducted research at Sanglah Hospital Denpasar with the results of a decrease in cognitive function scores on nurses with a shift work system [5], [8].…”
Section: Discussionsupporting
confidence: 92%
“…Signals from retina will be forwarded to an SCN oscillation system in the hypothalamus through the TRH tract. Giving blue light that has short waves (466-477 nm) at night is known to reduce melatonin levels in the blood and is associated with an increase in attention function and concentration [3], [4], [5]. Orexin is known to be associated with attention function, alertness, and concentration in awake conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuwanda, 2020 17 Hubungan antara lokasi stroke dengan gangguan kognitif pada penderita stroke Di RSUP Sanglah Denpasar Cross sectional/ Ina-MoCA Didapatkan diantara 80 sampel terdapat 60 (75%) pasien dengan gangguan fungsi kognitif. Gangguan kognitif lebih banyak terjadi pada pasien dengan lokasi stroke hemisfer kiri yaitu sebanyak 32 (53,33%) pasien.…”
Section: Gambaran Hipertensi Dengan Kejadian Demensia Vaskular Pada Pasien Stroke Non Hemoragik DI Poli Saraf Rsud Sultan Syarif Mohamad unclassified
“…Hanas et al 8 mendapatkan adanya hubungan antara lokasi lesi dengan penurunan fungsi kognitif pada pasien pasca stroke dengan nilai p=0,006 (p<0,05). Selain itu, penelitian oleh Windani 10 dan Yuwanda et al 17 mendapatkan bahwa adanya gangguan kognitif pada pasien stroke dengan lesi hemisfer kiri lebih banyak daripada lesi hemisfer kanan. Hanas et al, 8 Windani, 10 dan Chaurasia et al 14 melaporkan bahwa gangguan kognitif lebih banyak terjadi pada pasien pasca stroke iskemik daripada yang hemoragik.…”
Section: Bahasanunclassified